Lactose quantification in UHT milk by high-performance liquid chromatography and cryoscopy (freezing point depression) (Research, Society and Development, 2021)
Due to the large number of people with lactose maldigestion, the dairy industries have increased production and diversity of low lactose and lactose-free foods. Consequently, the need to control the lactose hydrolysis process has also risen. This study aimed to correlate freezing point depression (cryoscopy) and lactose concentration, quantified by high-performance liquid chromatography (HPLC), in UHT milk. To accomplish this, UHT milk samples were subjected to seven lactose hydrolysis treatments, using lactase enzyme, resulting in different lactose concentrations. All samples were subjected to HPLC analysis and freezing point measurement, using a cryoscope. The results were plotted on a graph and a linear regression was performed. There was a strong correlation between lactose concentration and freezing point (R = 0,9973) and the coefficient of determination (R2) was 0,9946, which means that 99,46% of the variability of the response data is explained by the linear regression model. Therefore, the results point to the feasibility of estimating the lactose concentration in milk during the hydrolysis process for the production of low lactose milk, by cryoscopy, a quick analysis, with lower cost compared to HPLC and that is already among the analyses commonly performed in dairy industries.